Hubungan Intensitas Penggunaan Gawai dan Tingkat Konsumsi Energi dengan Status Gizi Lebih pada Siswa SMA di Sidoarjo - Aghnia Ilmi Imani; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2023)
Background: Excessive use of gadgets can lead to a decrease in physical activity and an increase in consumption of high-energy foods which if it occurs over a long period of time will lead to overweight. Overweight can cause reduction on physiological conditions and mental health. Objectives: Knowing the relationship between intensity of using gadgets and level of energy consumption with overweight of high school students in Sidoarjo Methods: This study was a case-control design. The research was conducted on high school students in Sidoarjo taken from SMA Negeri 1 Sidoarjo, SMA Negeri 2 Sidoarjo, and SMA Negeri 3 Sidoarjo. The total sample required was 92 students with each group, overweight group and normal nutrition group, was 46 students. Sampling using stratified random sampling with the population was 2582 students. Data collection through questionnaires using gadgets, 24H Food Recall, and measurements of height and weight by researchers. Data were analyzed using the Chi-Square test with a significance level of 95%. Results: Majority of high school students in Sidoarjo, both with overweight (84.8%) and normal nutritional (73.9%), have moderate intensity of using gadgets. Level of energy consumption in the overweight group was more in the overcategory (54.3%), while in the normal nutrition group was in the sufficient category (87%). There was a relationship between level of energy consumption (p=<0.001; OR=7.937) and there is no relationship between the intensity of using gadgets (p=0.303) with overweight of high school students in Sidoarjo. Conclusions: The level of over energy consumption will be more at risk of experiencing more nutritional status compared to the level of sufficient energy consumption.This research needs further research with the addition of other variables.